Theme Shifts Found in English-Indonesian Translation of Newspaper Article by the Translation Students of English Department UNP - Titis Grahita; Don Narius (Universitas Negeri Padang, 2019)
This study analyzed type of themes in source text (ST) and target text (TT), also theme shifts in students’ translation product which are under Systemic Functional Linguistics (SFL) proposed by Halliday and Matthiessen (2004). The participants of this research were translation students of English education program of UNP that registered in academic year 2015. They were asked to translate newspaper article which published by The Jakarta Post from English into Bahasa Indonesia. Furthermore, descriptive qualitative research is applied. Based on the research findings, the researcher found that: (i) simple un-marked theme (SUT) was the theme most frequently used in both the ST and the TT; (ii) Students mostly did the theme shifts in the same-level of clause.